How actions emerge from innovation platforms—group feedback - Duncan, Alan J. (International Livestock Research Institute, 2011)
In early May 2011, people working on the Nile Basin Development Challenge (http://nilebdc.org) met in Addis Ababa in a 'science and reflection workshop'. Session 2 of the workshop examined institutional and other processes that are key to success of the overall program. In this video, Alan Duncan (ILRI) reports from small group discussions on how development actions should emerge out of innovation platforms in the NBDC.